MENINGKATKAN AKTIVITAS, KETERAMPILAN KOLABORASI DAN BERPIKIR KRITIS MENGGUNAKAN MODEL PANDAI PENDIDIKAN PANCASILA - Nadiatul Munawarah, Yogi Prihandoko, Noorhapizah & Darmiyati (STKIP Paris Barantai, 2025)
The low levels of learning outcomes, critical thinking, teamwork, and student engagement among fourth-grade children at SDN Kuin Cerucuk 4 served as the impetus for this study. The PANDAI paradigm, which combines Problem-Based Learning, Numbered Heads Together, and Group Investigation, was put into practice to address these problems. The objective was to enhance these elements through four meetings of Classroom Action Research (CAR), a qualitative method. Twenty-six students participated in the study. Written assessments for learning outcomes and critical thinking as well as observation for student participation and teamwork were used to gather data. The findings demonstrated a notable improvement: critical thinking rose from 27% to 85% and student engagement rose from 38% to 92%. The PANDAI model is suggested as an alternate strategy to raise the caliber of learning since it successfully raises student achievement and engagement. Keywords: Activity, Collaboration, Critical Thinking, PANDAI